3(x – 2) – 2x = x – 6
3x-6-2x=x-6
3x-2x-x=-6+6
no x's=0
0=0
2007-01-21 03:22:35
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Why is there a dot before the 3?
Solve 3(x – 2) – 2x = x – 6
First: eliminate the parenthesis - multiply the outer term with the terms in the parenthesis....
3(x ) - 3(2) - 2x = x - 6
3x - 6 - 2x = x - 6
x - 6 = x - 6
Sec: add "6" to both sides....
x - 6 + 6= x - 6 + 6
x = x - 0
x = x
Third: there are an infinite amount of solutions.
2007-01-21 09:18:25
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
3(x-2)-2x = x - 6
3x - 6 -2x= x - 6
x - 6 = x - 6
Both the Sides are same so it is an identity.
The Solution set for this is all real numbers.
2007-01-21 03:22:58
·
answer #3
·
answered by xeonforever 2
·
1⤊
0⤋
the answer is
how i got it=
.3x - .6 - 2x = x - 6
subtract .3x from both sides
-.6 - 2x = .7x - 6
add 2x to both sides
-.6 = 2.7x - 6
add 6 to both sides
5.4 = 2.7x
multiply each by 10 to get rid of decimals (makes it easier)
54 = 27x
divide each side by 27
x=2
I hope i helped becuase this took me a long time
check your answer
.3 (2 - 2) -2 * 2 = 2 - 6
.6 - .6 - 4 = 2 - 6
.6 - .6 -4 = -4
cancel out the -.6's
-4 = -4
im 13 and i can figure this out!!
2007-01-21 03:27:48
·
answer #4
·
answered by my # is 1-800-you-wish 3
·
0⤊
1⤋
3(x – 2) – 2x = x – 6?
ANS: 3x-6-2x=x-6
3x-2x=x-6+6
3x-2x=x
x=x
Therefore, left hand side is equal to right hand side.
2007-01-21 03:24:55
·
answer #5
·
answered by Mikhil M 2
·
1⤊
0⤋
I really have no clue let me try...... x = x
3(x-2)-2x=x-6
3x-6-2x=x-6
3x-6+6-2x=x-6+6
3x-2x=x
x=x
2007-01-21 03:26:39
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
3x-6-2x=x-6
x-6=x-6
x=x or 0=0
and im only 12!
2007-01-21 03:27:18
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋
this is impossible because x-2 does not equal x-6. then you would get 0 equals -4 which isn't true either.
2007-01-21 03:21:22
·
answer #8
·
answered by Anonymous
·
0⤊
2⤋
You tricky, tricky white girl! (credit to Everybody Loves Raymond show). It's not nice to have someone else do your homework.
lightpulse
2007-01-21 03:35:00
·
answer #9
·
answered by lightpulse 4
·
0⤊
1⤋
0.3x - 0.6 -2x = x - 6
-2.7x = 0.6 - 6
x = -5.4/-2.7
x = 2
2007-01-21 03:27:58
·
answer #10
·
answered by Anonymous
·
0⤊
1⤋